The Nijmegen Method of Case Deliberation and Clinical Decision in a Multicultural Society - Kazeem, Fayemi Ademola (Bangladesh Journal of Bioethics, 2014)
The Nijmegen method of ethical case deliberation is one of the ways of reflecting, clarifying, evaluating and making decisions about moral problems, conflicts and dilemmas in the clinical settings. It is a hybrid concentration of relevant ideas from different normative ethical traditions applied to the clinical practices. As a team multidisciplinary based deliberation, the method involves a professional ethicist serving as both a critical tutor and a facilitator in the process of deliberating and arriving at most ethical decision in clinical dilemmas. In such process, the Nijmegen method is not a democratic replacement of the decision and responsibility of the healthcare team. Rather it helps to motivate rational decision and reasoned responsibility in healthcare through consensus building which does not attenuate moral uprightness. The Nijmegen method is part of the healthcare process and aims at improving communication among patient, family and the healthcare team as well as enriching the decision making process. It is a promising method in resolving moral dilemmas in healthcare especially in multicultural societies. Besides enhancing the quality and transparency of the decision making process, ethical case deliberation on the ward using the Nijmegen method has prospect of serving as a baseline in guiding through similar dilemmas in the future. DOI: http://dx.doi.org/10.3329/bioethics.v5i2.19618 Bangladesh Journal of Bioethics 2014 Vol.5(2):73-79